Organizational Rigidity and Demands: A Qualitative Study on Nursing Work in Complex Organizations - Julia van Kraaij; Frits van Merode; Emma Lenssen; Hester Vermeulen; Catharina van Oostveen; RN2Blend Consortium (Nursing Reports)
Background/Objectives: The nursing work environment is a critical element in healthcare delivery and a strong predictor of both patient and nurse outcomes. Understanding the complexity and multifaceted nature of this environment is essential for improving nursing practices and optimizing healthcare systems. This study aimed to gain insights into the perceived characteristics of the nursing work environment, considering it as a complex and multifaceted system. Methods: A qualitative research approach was employed, involving 42 semi-structured interviews with 43 nurses and managers from academic, teaching, and general hospitals in The Netherlands. Data were collected between July 2020 and August 2021 through convenience sampling. Thematic coding was conducted to identify key patterns and themes. Results: The findings revealed that nurses demonstrated flexibility and a strong commitment to high-quality care, despite grappling with rigorous organizational tasks and processes. Four key themes emerged: (1) direct patient care as a standard feature of nursing work; (2) nurses’ flexibility for hospital productivity; (3) interdependencies, which decrease autonomous nursing practices; and (4) organizational structures that determine how nurses can shape their work. Nurses found it difficult to balance direct care with broader tasks due to organizational rigidity, revealing a gap between ideal nursing practices and daily reality. Conclusions: This study highlighted the challenges within the nursing work environment, particularly in balancing direct care with organizational demands. Addressing this gap between ideal nursing practice and reality requires a systems approach. This includes autonomous practices, supportive management, and flexible structures, allowing nurses to shape their work and enhance job satisfaction and care quality.